2019
DOI: 10.1177/0960327119851252
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and its CD4+ and CD8+ subgroup changes after paraquat poisoning

Abstract: Objective: Paraquat (PQ) poisoning is a significant cause of mortality and morbidity in developing countries. Poor prognostic outcomes have been attributed to the herbicide’s toxicity and the lack of effective treatments. Our study aims to investigate the changes in lymphocyte count in both patients who survived and died from PQ poisoning and explore the prognostic value. Method: This is a retrospective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…An unfavourable consequence of paraquat poisoning is predicted when taking large doses of a concentrate or solutions with a significant amount of it orally, if a high content of the herbicide in blood plasma and urine is determined, as well as in the case of early development of multiple organ failure and severe alveolitis [1-9, 18,40]. Analysing 130 clinical observations of acute paraquat poisoning, of which 35 (26,8%) were fatal, it was found that an important indicator for such a prognosis is also the severity of immunity disorders, including changes in the number of CD4 + and CD8 + lymphocytes [46].…”
Section: Problem Articlesmentioning
confidence: 99%
“…An unfavourable consequence of paraquat poisoning is predicted when taking large doses of a concentrate or solutions with a significant amount of it orally, if a high content of the herbicide in blood plasma and urine is determined, as well as in the case of early development of multiple organ failure and severe alveolitis [1-9, 18,40]. Analysing 130 clinical observations of acute paraquat poisoning, of which 35 (26,8%) were fatal, it was found that an important indicator for such a prognosis is also the severity of immunity disorders, including changes in the number of CD4 + and CD8 + lymphocytes [46].…”
Section: Problem Articlesmentioning
confidence: 99%
“…Несприятливий наслідок при отруєнні паракватом прогнозується при пероральному прийомі великих доз його концентрату або розчинів із значним його вмістом, якщо визначено високий вміст гербіциду у плазмі крові та сечі, а також у разі раннього розвитку поліорганної недостатності та вираженого альвеоліту [1-9, 18, 40]. Аналізуючи 130 клінічних спостережень гострого отруєння паракватом, з яких 35 (26,8%) завершилися летально, встановлено: важливим показником для такого прогнозу також є ступінь вираженості порушення імунітету, в тому числі зміна числа СД4 + і СД8 + лімфоцитів [46].…”
Section: проблемні статтіunclassified